SISTEM PENDUKUNG KEPUTUSAN PENEPATAN PEGAWAI YANG AKAN DIPROMOSIKAN MENGGUNAKAN METODE MULTIFACTOR EVALUATION PROCESS PADA KANTOR BKPSDM KABIPATEN LEBONG - Lia Veranica; Sapri Sapri; Devi Sartika (Smart Education, 2023)
Determination of employees who are promoted to positions aims to provide motivation and positive influence on other employees to further improve the work ethic in the Lebong District Regent's office. Determining who will be famous for mutation/promotion has of course gone through various stages of the process from within the Committee Team as well as passing the evaluation stages from the Committee based on certain criteria that have been set. These criteria include class (I, II, III and IV), tenure (long, long and recent), last education (Diploma, S1 and S2), training (1-3, 3-5, > 5) achievement (low, medium, high, and very high) and time period (short, medium and long). Lebong Regency Government Offices who meet the highest criteria will be selected to get a promotion for their dedication. However, the problem is how to make the right and competent choice as an employee who has high dedication if in the assessment alone there are employees who have almost the same rating score, close to the same, or even the exact same. It will be difficult for the Committee to make a decision to determine which employees are promoted to positions. Therefore, a Decision Support System with the application of the MFEP (Multifactor Evaluation Process) method can assist in making decisions on complex issues by simplifying the process. This system can assist decision makers in determining promotions quickly and precisely.